Financial Literacy, Lifestyle, And Parental Income On Financial Management Behavior With Self-Control As A Mediating Variable (Case Study of College Students in Malang City) - Nadia Rahma Farikha; Farahiyah Sartika (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of financial literacy, lifestyle, and parental income on financial management behavior, with self-control as an intervening variable among college students in Malang City. Using a quantitative explanatory research approach, data were collected through questionnaires from 160 respondents and analyzed using SEM-PLS. The results showed that financial literacy, lifestyle, and parental income had a positive and significant effect on financial management behavior. Furthermore, self-control also significantly influenced financial management behavior. However, self-control only mediated the relationship between parental income and financial management behavior, and was unable to mediate the influence of financial literacy and lifestyle. This indicates that college students' financial management behavior is more directly influenced by financial knowledge, lifestyle, and financial support from parents. This study implies that improving financial literacy and self-control needs to be strengthened to support better financial management.